Pengaruh Motivasi terhadap Kinerja Guru melalui Disiplin Kerja pada SMK Binakarya Mandiri Kota Bekasi - Lisa Ameliya; Supardi Supardi; Agus Dharmanto (Journal Economic Excellence Ibnu Sina, 2024)
The aim of this research is to determine the effect of motivation on teacher performance through work discipline at Binakarya Mandiri Vocational School, Bekasi City. This research uses a quantitative type of research. There are two types of data used in this research, namely primary data and secondary data. Data is collected through preparing statements that will be submitted and answered by respondents in the form of a questionnaire. The population was all teachers at Binakarya Mandiri Vocational School, Bekasi City, totaling 100 teacher, and this research used a saturated sample. Then, the data that has been collected will be processed using the Statistical Product and Service Solutions (SPSS) program version 26. The conclusions of this research are as follows : 1. Motivation on teacher performance has an influence on Binakarya Mandiri Vocational School, Bekasi City. This states that a teacher who always attends teacher meetings at school is very important in carrying out his duties because of the support and development of teacher, so that teacher always provide examples to help students understand learning material, so motivation can improve teacher perfoemance. 2. Motivation towards work discipline has an influence on Binakarya Mandiri Vocational School, Bekasi City. This states that a teacher who always attends teacher meetings at school is very important in carrying out his duties because of the support and development of teacher so that teacher are always present on time at school and there is encouragement of teacher work enthusiasm and responsibility, so motivation can improve work discipline. 3. work discipline on teacher performance has an influence on Binakarya Mandiri Vocational School, Bekasi City. This states that a teacher is always present at school on time, so the teacher always provides examples to help students understand the learning material in order to achieve goals, so that work discipline can improve teacher performance. 4. The results of the path analysis test show that the total influence value is greater than the direct influence, so that work discipline can function as a mediating variable between motivation and teacher performance at Binakarya Mandiri Vocational School, Bekasi City.